The Impact of Public Employment on Labor Market Performance : Evidence from African Countries - Ranzani, Marco; Tuccio, Michele (Taylor and Francis, 2016)
Using census data for Ghana, Mali and Mozambique, we study the long-term impact of public sector employment on local labor markets. We find that the public sector crowds out private employment and induces skilled workers to queue for a public job, thus increasing their unemployment rate. In addition, a growing public sector fosters employment in the tradable and nontradable sectors, remarkably for the unskilled, and the reallocation of unskilled workers away from agriculture.